An Analytical of the Design Process of Special Economic Zone Governance in Indonesia: Special Economic Zone Study of Arun Lhokseumawe - Muzwardi*, Ady; Fera, Mirta; Maryam, Siti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
Arun Lhoksumawe Special Economic Zone is an economic zone established as one of the economic growth centers of Aceh Province. In the planning, pre-operational, and operational processes, Arun Lhoksumawe Special Economic Zone still faces several significant problems. Therefore, the purpose of this qualitative research is to analyze the process of designing the governance of the Special Economic Zone. This analysis process is carried out through observation with secondary data from 2018 to 2019 as research support. The results of this study show that there are weaknesses in asset management that are not proportionally distributed so that collaboration and integration of assets are needed for the optimization of the Arun special economic zone. So, the results of this study can be used as evaluation material to optimize the Arun Lhoksumawe special economic zone. Keyword: Special Economic Zones; Interest Groups; Co-operation; Assets; Arun